Molecular and genotyping for Cryptosporidium parvum isolated from children with diarrhea in pediatric hospital of Karbala - Ahmed Hussain Mibder1, Ghada B. Al-Omashi1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The study involved surveilling sampling of children suffered cryptosporidiosis like symptoms.The present study was conducted on 90 children who suffer from abdominal pain and diarrhea .Samples were collected from patients suspected infection by cryptosporidium who attended in pediatric hospital of Karbala Governorate from January-2019 to May 2019,They were (1month-5 years old age). Each sample was divided into two parts. The first part was used to prepared a moderate thick smears stained with modified zehil nelson stain(m ZN stain)and the second part was preserved at -20 c for molecular detection by nested PCR to identify the positive samples and genotyping by RFLP-PCRthat showed the PCR product analysis of HSP70 gene in Cryptosporidium parvum from Human stool samples, at (587bp) PCR product.Some positive samples by RFLP-PCR making nucleic acid sequencing.The. main. Purpose. of .the .current. study. was. to explore the prevalence rate of cryptosporidiosis in the mentioned province targeting children at different age categories of both genders. For the gender and infection by C. parvum, the current work findings .revealed. the. presence. of. C. parvum .in. the sampled children distributed under gender categories of male and female and the species was parvum .The results of the AFS showed that 12 (13.33%) out of 90 samples were positive to the presence of cryptosporidiosis. This technique is a good method for detecting C. parvumin stool samples of children in both genders, and 27 out of 90 samples was positive by nested PCR and RFLP-PCR respectively. For the age and infection by C. parvum, the current work findings revealed. the. presence .of .C. parvum .in .the. sampled children distributed under three age categories of 1-6 months, 7-12 months, and 13-60 months. Positive results of the age categories were 5 (29.41%) out of 17 samples, 12 (32.43%) out of 37 samples, and 10 (27.78%) out of 36 samples, respectively. The total infection was 27 (30%) out of 90 samples. No significant (p?0.05) differences were recognized for infection rates occurred for the age categories.